Alpelisib in combination with everolimus ± exemestane in solid tumours: Phase Ib randomised, open-label, multicentre study - Curigliano, Giuseppe; Martin, Miguel; Jhaveri, Komal; Beck, J.T.; Tortora, Giampaolo; Fazio, Nicola; Maur, Michela; Hubner, Richard A.; Lahner, Harald; Donnet, Valerie; Ajipa, Olga; Li, Zheng; et al. (European journal of cancer (1990), 2021)
Combined mTORC1 inhibition with everolimus (EVE) and phosphatidylinositol 3-kinase catalytic subunit p110α blockade with alpelisib (ALP) has demonstrated synergistic efficacy in preclinical models and supports testing the combination of ALP and EVE in the clinical setting. The primary objective was to determine the maximum tolerated dose (MTD)/recommended dose for expansion (RDE) of ALP in combination with EVE and in combination with EVE and exemestane (EXE) and subsequently assess safety, preliminary efficacy and effect of ALP on the pharmacokinetics of EVE and determine the magnitude of the drug-drug interaction. Dose escalation phases were conducted in patients with advanced solid tumours and in postmenopausal women with hormone receptor–positive (HR+), human epidermal growth factor receptor 2–negative (HER2–) advanced breast cancer (ABC). The dose expansion phase was conducted in patients with pancreatic neuroendocrine tumour and renal cell carcinoma (RCC) (both mechanistic target of rapamycin inhibitor [mTORi]–naive), in patients with mTORi-pretreated solid tumours and in postmenopausal women with HR+, HER2– ABC. During the doublet escalation phase, dose-limiting toxicities (DLTs) were reported in 5 of 10 (50%) patients: one patient had grade (Gr) 2 hyperglycemia and one patient had Gr 3 diarrhoea in the 300 mg dose group, one patient had Gr 2 hyperglycemia and one patient had Gr 4 hypocalcaemia in the 250 mg dose group, and one patient in the 200 mg dose group had Gr 3 diarrhoea and Gr 3 stomatitis. The combination of ALP 250 mg + EVE 2.5 mg was declared as the MTD/RDE in subjects with advanced solid tumours. In the triplet escalation phase, one patient who received ALP 200 mg + EVE 2.5 mg + EXE 25 mg had a DLT of Gr 3 acute kidney injury. This dose combination was declared as the MTD and RDE in subjects with advanced HR-positive HER2-negative BC. The common adverse events (≥30% patients), occurring across all phases, were hyperglycaemia, stomatitis, diarrhoea, nausea, asthenia, decreased appetite and fatigue. The sixteen-week progression-free survival rate was 52.4% (90% confidence interval [CI]: 32.8, 71.4) in the RCC cohort, 35.3% (90% CI: 16.6, 58.0) in the prior pNET cohort and 30.0% (90% CI: 8.7, 60.7) in the prior mTORi cohort. The pharmacokinetics of 2.5 mg of EVE was largely unchanged in the presence of ALP, independent of the dose (250 mg or 300 mg). There were no clinically relevant drug-drug interactions observed between ALP and EVE. The overall safety profile of ALP with EVE and EXE is manageable and reversible; no unexpected safety signals were noted compared with the individual safety profiles. Pharmacokinetics of ALP, EVE and EXE was largely unchanged in combination with each other. •Everolimus and alpelisib are synergistic in preclinical models.•The pharmacokinetics of everolimus was unchanged in the presence of alpelisib.•The combination of alpelisib and everolimus was active in advanced solid tumors.